2020
DOI: 10.1097/gox.0000000000002605
|View full text |Cite|
|
Sign up to set email alerts
|

Mid-Term Outcome after Selective Neurotization of the Infraspinatus Muscle in Patients with Brachial Plexus Birth Injury

Abstract: Background: Active shoulder external rotation in adduction can be restored by selective neurotization of the infraspinatus muscle with the spinal accessory nerve in select patients with brachial plexus birth injury. Does the improved shoulder external rotation stand the test of time? Methods: Fourteen consecutive brachial plexus birth injury patients with active shoulder external rotation in adduction of ≤ 0 degrees and active shoulder elevation ≥ 90 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…A congruent shoulder with normal ROM is a prerequisite for subsequent tendon or nerve transfers, which underlines the importance of early diagnosis and treatment of posterior shoulder dislocation. Shoulder ER can be improved by various tendon or nerve transfers (Bahm et al., 2005; Elhassan, 2014; Grahn et al., 2020; Grossman et al., 2004; Soldado, 2020; Waters et al., 2008) and several authors advocate surgery to restore missing external rotation before 3 years of age in order to maintain shoulder congruence and prevent development of glenohumeral deformity (Hui and Torode, 2003; Pearl et al., 2003; Van Heest et al., 2010; Vuillermin et al., 2020; Waters and Bae, 2008). One of the reasons for our decreased rate of relocation is an improved understanding and a more active approach in keeping the shoulder in place, aimed at restoring active function before 3 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A congruent shoulder with normal ROM is a prerequisite for subsequent tendon or nerve transfers, which underlines the importance of early diagnosis and treatment of posterior shoulder dislocation. Shoulder ER can be improved by various tendon or nerve transfers (Bahm et al., 2005; Elhassan, 2014; Grahn et al., 2020; Grossman et al., 2004; Soldado, 2020; Waters et al., 2008) and several authors advocate surgery to restore missing external rotation before 3 years of age in order to maintain shoulder congruence and prevent development of glenohumeral deformity (Hui and Torode, 2003; Pearl et al., 2003; Van Heest et al., 2010; Vuillermin et al., 2020; Waters and Bae, 2008). One of the reasons for our decreased rate of relocation is an improved understanding and a more active approach in keeping the shoulder in place, aimed at restoring active function before 3 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, selective transfer of the SAN to the infraspinatus branch of the SSN has been described in patients with congruent glenohumeral joints with encouraging results: a preliminary series showed that 86% of patients had active external rotation greater than 20 degrees beyond the sagittal plane. 65…”
Section: Distal Nerve Transfers (Neurotization)mentioning
confidence: 99%
“…the infraspinatus branch of the SSN has been described in patients with congruent glenohumeral joints with encouraging results: a preliminary series showed that 86% of patients had active external rotation greater than 20 degrees beyond the sagittal plane. 65 To date, no studies have convincingly demonstrated improved active external rotation when comparing the outcomes of SAN-to-SSN transfer versus nerve grafting; in fact, earlier studies with at least 3 years of follow-up demonstrated that both techniques resulted in suboptimal improvement in external rotation [59][60][61] (Table 3). More recent data continue to show poor outcomes for external rotation with both nerve grafting and nerve transfer, with mean postoperative AMS scores for both groups below the threshold of functionally meaningful active motion (AMS ≥ 6).…”
Section: Ementioning
confidence: 99%
“…Grahn et al 46 , em 2020, publicam um estudo com 14 casos de transferência do nervo acessório (XI) para o ramo motor do músculo infraespinal.…”
Section: Renata Gregorio Paulosunclassified
“…Devido a isso, alguns artigos recentes propuseram transferência nervosa seletiva para atingir rotação externa ativa do ombro[45][46][47] . Os três estudos encontrados na literatura têm como alvo crianças com mais de 18 meses que tiveram boa recuperação nervosa espontânea, com exceção do ganho ativo de rotação externa do ombro.…”
unclassified